Characterization of Plasma Membrane Ceramides by Super‐Resolution Microscopy. Issue 22 (5th April 2017) - Burgert, Anne; Schlegel, Jan; Bécam, Jérôme; Doose, Sören; Bieberich, Erhard; Schubert‐Unkmeir, Alexandra; Sauer, Markus
Abstract: The sphingolipid ceramide regulates cellular processes such as differentiation, proliferation, growth arrest, and apoptosis. Ceramide‐rich membrane areas promote structural changes within the plasma membrane that segregate membrane receptors and affect membrane curvature and vesicle formation, fusion, and trafficking. Ceramides were labeled by immunocytochemistry to visualize their distribution on the plasma membrane of different cells with virtually molecular resolution by direct stochastic optical reconstruction microscopy ( d STORM). Super‐resolution images show that independent of labeling conditions and cell type 50–60 % of all membrane ceramides are located in ceramide‐rich platforms (CRPs) with a size of about 75 nm that are composed of at least about 20 ceramides. Treatment of cells with Bacillus cereus sphingomyelinase (bSMase) increases the overall ceramide concentration in the plasma membrane, the quantity of CRPs, and their size. Simultaneously, the ceramide concentration in CRPs increases approximately twofold. Abstract : dSTORM microscopy reveals that, independent of the cell‐type, membrane ceramides form nanodomains (CRPs) with a diameter of about 75 nm containing 50–60 % of all ceramides. Treatment with sphingomyelinase increases the quantity of ceramides, the size and density of CRPs as well as the ceramide concentration in CRPs.